First evidence for a possible invasional meltdown among invasive fish parasites. Issue 1 (December 2018) - Hohenadler, M.; Honka, K.; Emde, S.; Klimpel, S.; Sures, B.
Abstract Biological invasions are frequently studied topics in ecological research. Unfortunately, within invasion ecology parasite-associated aspects such as parasite impacts on new environments and on local host populations are less well-studied. Round gobies migrating from the Ponto-Caspian region into the Rhine River system are heavily infested with the Ponto-Caspian acanthocephalan parasitePomphorhynchus laevis . As shown by experimental infestations the acanthocephalans occur as pre-adults in host-encapsulated cysts within the internal organs of the migrating gobies, but remain infective for their definitive host chub. Recently, we described the occurrence of larvae of another parasite, the invasive eel swim bladder nematodeAnguillicola crassus, in thesePomphorhynchus cysts. In the present study, we could prove the infectivity of the nematode larvae for European eels for the first time. After experimental inoculation ofPomphorhynchus cysts occasionally infested withA .crassus larvae, the nematodes grow to maturity and reproduce whereas allP .laevis were unviable. We therefore postulate that the nematode larvae behave like immunological hitchhikers that follow a "Trojan horse strategy" in order to avoid the paratenic host's immune response. Accordingly, the interaction between both invasive parasites gives first evidence that the invasional meltdown hypothesis may also apply to parasites.